2017
DOI: 10.1152/ajprenal.00539.2016
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal signaling mediated by CCK plays a role in salt intake-induced natriuresis

Abstract: The natriuretic hormone CCK exhibits its gene transcripts in total kidney extracts. To test the possibility of CCK acting as an intrarenal mediator of sodium excretion, we examined mouse kidneys by ) an in situ hybridization technique for CCK mRNA in animals fed a normal- or a high-sodium diet;) immuno-electron microscopy for the CCK peptide, ) an in situ hybridization method and immunohistochemistry for the CCK-specific receptor CCKAR;) confocal image analysis of receptor-mediated Ca responses in isolated ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The analysis also identified some GPCRs without well-characterized kidney functions including cholecystokinin A receptor (Cckar) in PT. A recent study indicated that it might regulate proximal tubular reabsorption 40 . Additional analyses were provided in this study including the distribution of aquaporins ( Supplementary Fig.…”
Section: Transcriptomic Landscape Of Microdissected Ctal Dct and Cntmentioning
confidence: 99%
“…The analysis also identified some GPCRs without well-characterized kidney functions including cholecystokinin A receptor (Cckar) in PT. A recent study indicated that it might regulate proximal tubular reabsorption 40 . Additional analyses were provided in this study including the distribution of aquaporins ( Supplementary Fig.…”
Section: Transcriptomic Landscape Of Microdissected Ctal Dct and Cntmentioning
confidence: 99%
“…CCK1R is expressed in the cerebral cortex and subcortical structures (basal ganglia, hippocampus, thalamus and hypothalamus) (1)(2)(3)(4)(5)(6)(7), in the brain stem and spinal dorsal horn (1)(2)(3). In the periphery, CCK1R is localized in trigeminal ganglia (8), the vagus (9,10), myenteric plexus (11), stomach (12,13), pancreas (12,14,15), gallbladder (12,16), intestines (17,18), adrenal cortex (19), kidney tubules (20), spleen (21), white adipose tissue (22) and leukocytes (23). Central CCK1R regulates peptide neurotransmitter release (24,25), anxiolysis (26)(27)(28), appetite (29), neurogenesis (4,30), learning and memory (31).…”
Section: Introductionmentioning
confidence: 99%